ANALISIS KENDALA EKSTERNAL DALAM PENULISAN KARYA ILMIAH SISWA - Hartati, Rahma Dewi; Pratiwi, Brillianing (Dialektika: Jurnal Bahasa, Sastra, dan Pendidikan Bahasa dan Sastra Indonesia, 2024)
In the process of learning Indonesian scientific paper materials, one of the core competencies is the ability to compile and convey complete scientific findings through written papers. However, many students face difficulties when it comes to the writing process. This study aims to understand the learning process of scientific paper writing in the classroom, analyze the factors that contribute to students' struggles in developing scientific papers, and describe the challenges that students face. The research involved high school students who were studying scientific work materials. Qualitative research with descriptive analysis methods was used to gather data. The study revealed that external factors have a considerable impact on students struggling with writing scientific papers. These factors encompass a classroom atmosphere with insufficient learning support, an unsuitable learning environment for scientific paper writing, and inadequate provisions for planning and delivering appropriate learning materials.